Religiosity and corporate financial reporting: evidence from a European country. Issue 1 (2nd January 2017) - Montenegro, Tânia Menezes
Abstract: Using a sample of Portuguese firms, I examine the association between religiosity and financial reporting quality. The results suggest that firms headquartered in areas with strong religious adherence, higher levels of (aggregate) religiosity, and in the core area of the Portuguese religious cult (the district where the Fátima Sanctuary is located) generally experience lower incidence of earnings management. The evidence on religious adherence holds separately for Catholic affiliation, and the results are not driven by firms headquartered in rural areas. I also conclude that religiosity, together with other forms of external monitoring, represents a mechanism for reducing aggressive accounting practices. I confirm that the evidence on the positive association between religiosity and financial reporting quality previously gathered from a primarily Protestant country (US) and from a Buddhist and Taoist country (China), holds in the Latin Europe, which is dominated by the Catholic denomination and has a lower intensity of religiosity.